Identity of Street Homeless People: A General Review - Joshi, Sudarshan (Research Nepal Journal of Development Studies, 2020)
The people, who live, eat, and conduct activities in street and public places are street homeless people. It is simply based in observation because street homeless people do not want to disclose their identity. The study is generally the qualitative library based literature review on the issues of understanding homelessness. The main objective of the study is to collect the different meanings fusing the horizon in the application to Nepalese Homelessness. The study has reviewed 109 articles. Normally poor, destitute, and mentally weak people find in street as homeless. They need proper care and absolute identity. In the context of Nepal people found in street like street children, women and mentally weak people who live and survive in street and public places are street homeless people of Nepal.